Learning About Situational Crime Prevention From Offenders: Using a Script Framework to Compare the Commission of Completed and Disrupted Sexual Offenses. (December 2019) - Cook, Alana; Reynald, Danielle M.; Leclerc, Benoit; Wortley, Richard
The collective knowledge of offenders is one of the richest ways to advance understandings of crime commission and effective crime prevention. Drawing on self-report data from 53 incarcerated offenders in three Australian states and territories, the current article presents an innovative method which, through a crime script framework, allows for a first-time comparison of completed versus disrupted sexual offenses involving adult female and child victims at each stage of the crime commission process. Findings (a) highlight the critical need to boost the efficacy of situational prevention in the crime setup phase of the sexual offense script and (b) showcase how incorporating a script framework in offender-based research can identify new directions for crime prevention